2010
DOI: 10.1055/s-0030-1258138
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Multicomponent Synthesis of Polysubstituted Pyrrolidines and Tetrahydropyrimidines Starting Directly from Nitro Compounds in Water¹

Abstract: A distinct approach for the synthesis of 1,3,3-trisubstituted 4,5-dioxopyrrolidines and 1,3,4,5-tetrasubstituted 1,2,3,6-tetrahydropyrimidines has been discovered, in the form of a threecomponent reaction of nitroarenes, formaldehyde, and dialkyl acetylenedicarboxylates using indium in dilute aqueous HCl at room temperature. The molar ratios of these substrates are 1:1:4 and 2:1:4 for the preparation of dioxopyrrolidines and tetrahydropyrimidines, respectively. The reactions involve the reduction of nitro comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 1 publication
0
13
0
Order By: Relevance
“…Our literature survey at this stage revealed that there are some reports [18][19][20][21][22] on the synthesis of tetrahydropyrimidine derivatives containing an ester group in position 5. Khan and coworkers reported [18] the synthesis of substituted tetrahydropyrimidine and bis-tetrahydropyrimidine derivatives in good-to-excellent yields involving the reaction of dimethyl acetylenedicarboxylate, amines/diamines, and formaldehyde in the presence of (HClO 4 -SiO 2 ) as catalyst.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our literature survey at this stage revealed that there are some reports [18][19][20][21][22] on the synthesis of tetrahydropyrimidine derivatives containing an ester group in position 5. Khan and coworkers reported [18] the synthesis of substituted tetrahydropyrimidine and bis-tetrahydropyrimidine derivatives in good-to-excellent yields involving the reaction of dimethyl acetylenedicarboxylate, amines/diamines, and formaldehyde in the presence of (HClO 4 -SiO 2 ) as catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…It should be mentioned that the work reported by Khan et al used [20]. Also, Das et al described [21] a three-component reaction of nitroarenes, formaldehyde, and dialkylacetylenedicarboxylates for the synthesis of 1,3,4,5-tetrasubstituted 1,2,3,6-tetrahydropyrimidines using indium as catalyst in dilute aqueous HCl at room temperature. The authors further extended their work and reported a multicomponent synthesis of tetrahydropyrimidines employing iodine as catalyst [22].…”
Section: Introductionmentioning
confidence: 99%
“…Previous work that were reported for the synthesis of dioxopyrrolidines, generally involved higher reaction temperature, longer time period or hazardous catalysts. In one of those examples, Das and his group synthesised dioxopyrrolidines using HCl as catalyst . In addition, in another report, they synthesized the same products using I 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Das et. al. reported the synthesis of poly substituted pyrrolidines and tetra-hydropyrimidines involving indium as a catalyst in aqueous medium [17]. Zhu et.…”
Section: Introductionmentioning
confidence: 99%